Lrp5/6 are required for cerebellar development and for suppressing TH expression in Purkinje cells via β-catenin. Issue 1 (December 2016) - Huang, Ying; Zhang, Qiong; Song, Ning-Ning; Zhang, Lei; Sun, Yu-Ling; Hu, Ling; Chen, Jia-Ying; Zhu, Weidong; Li, Jue; Ding, Yu-Qiang
Abstract Background The cerebellum is responsible for coordinating motor functions and has a unique laminated architecture. Purkinje cells are inhibitory neurons and represent the only output from the cerebellar cortex. Tyrosine hydroxylase (TH) is the key enzyme for the synthesis of catecholamines, including dopamine and noradrenaline, and it is normally not expressed in cerebellar neurons. Results We report here that the low-density lipoprotein receptors (Lrp) 5 and 6, Wnt co-receptors, are required for the development of the cerebellum and for suppressing ectopic TH expression in Purkinje cells. Simultaneous inactivation of Lrp 5 and 6 by Nestin-Cre results in defective lamination and foliation of the cerebellum during postnatal development. Surprisingly, TH is ectopically expressed by Purkinje cells, although they still keep its other neurochemical characteristics. These phenotypes are also observed in the cerebellum of GFAP-Cre;β-cateninflox/flox mice, and AAV2-Cre-mediated gene deletion leads to ectopic TH expression in Purkinje cells of β-cateninflox/flox mice as well. Conclusions Our results revealed a new role of the canonical Lrp5/6-β-catenin pathway in regulating the morphogenesis of the cerebellum during postnatal development.